Colonic Perforation after Exchange Transfusion - Corkery, J. J. (1968)
Four patients are reported in whom perforation of the colon followed exchange transfusion for haemolytic disease of the newborn. This association seems to be more than coincidental, and possibly the perforation is due to a vascular accident occurring as a mechanical result of the exchange transfusion. The insidious onset of colonic perforation may be recognized early by the passage of blood per rectum. There is no place for conservative treatment, and once the diagnosis has been made treatment must include broad-spectrum antibiotics and laparotomy.